Devaluation and Competitiveness in a Small Open Economy : Ireland 1987-1993 - Bartolini, Leonardo (IMF Working Papers; Working Paper ;, 1993)
This paper studies market expectations of a devaluation of the Irish pound from 1987 to 1993 and relates them to the evolution of Ireland's competitiveness over the same period. Changes in expectations of the currency's devaluation can be explained largely by developments outside Ireland, particularly by past and anticipated movements of sterling. The evolution of Ireland's real exchange rate over the same period is also found to be strongly linked to sterling's fluctuations, even after adjusting for sterling-insensitive trade between Ireland and the United Kingdom, and despite the significant progress toward trade diversification recorded by Ireland during the 1980s. The devaluation of the Irish pound in January 1993 is estimated to exceed investors' realignment expectations at that time as well as the loss of Irish competitiveness since the beginning of the ERM crisis in the summer of 1992. This 'excess devaluation' helps explain subsequent large capital inflows and the Irish pound's smooth transition to the wide ERM band in August 1993.